ҚАЗАҚСТАН МЕН ҚЫТАЙ АРАСЫНДАҒЫ ЭНЕРГЕТИКАЛЫҚ РЕСУРСТАР МӘСЕЛЕСІ - Түргенбай, А. Ә.; Сманова, Н. (Journal of Oriental Studies, 2016)
В этом докладе рассматриваются главные пробле- мы, возникающие между Казахстаном и Китаем в связи с энергетическими ресурсами, и способы их решения. Кроме того, широко анализируются стратегические на- мерения и цели Китая в Казахстане. Наряду с этим в докладе всесторонне рассмат- риваются главные принципы внешней политики Китая, Вест ник КазНУ. Серия востоковедения. №3(56). 2011 41 которые они придерживаются относительно Казах- стана. The main problems arising in connection with energy resources between Kazakhstan and China and the methods of their solution are considered in this report. Besides that the China`s strategic intentions and aims in Kazakhstan are widely analyzed. At the same time the main principles of the foreign policy of China relatively to Kazakhstan are thoroughly considered in the report.